Efficacy of Topical Finasteride 0.5% vs 17α-Estradiol 0.05% in the Treatment of Postmenopausal Female Pattern Hair Loss: A Retrospective, Single-Blind Study of 119 Patients - Alfredo Rossi (Mattioli1885, 2020)
Background and Objectives: Female pattern hair loss (FPHL) is a common form of scalp hair loss that occurs in 38% of females. Currently, minoxidil solution is the only therapy approved by the US Food and Drug Administration, but many other treatments are used, including cyproterone acetate, spironolactone, topical 17α-estradiol, and prostaglandin analogs. Systemic finasteride has been considered a treatment option in women even though its teratogenic effects tend to limit its prescription. Recently, topical finasteride has been evaluated to limit the side effect profile of the drug. The objective of the present study is to compare retrospectively the efficacy of topical 0.05% 17α-estradiol solution and a 0.5% finasteride lotion in the treatment of FPHL.